Investigating the high-impact deformation behavior of induced-nano precipitation hardened in718 alloy - ONOVO, Harrison Okechukwu; BODUDE, Muideen Adebayo; ESEZOBOR, David Ehigie; AKANO, Thaddeus Tochukwu (Journal of Metals, Materials and Minerals, 2024)
Superalloys are the preferred materials for modern high-rotational complex components due to their exceptional ability to maintain critical properties such as strength, oxidation/corrosion resistance, even under extreme temperatures and dynamic impacts. This study investigates the dynamic impact response of nanoprecipitation-hardened 718 alloy (NPH-718 alloy) under various loading conditions. The wrought nickel-based NPH-718 alloy was transformed into a nanostructured state through a precise heat treatment process involving controlled cooling rates (28℃∙s‒1 to 30℃∙s‒1). A mechanical compression test, leading to failure, was employed to assess the alloy's ability to withstand dynamic impacts. The compressive dynamic behavior of the alloy at high strain rates (4000 s‒1 to 7500 s‒1) and temperatures ranging from ‒180℃ to 750℃ was evaluated using a custom-built direct impact Hopkinson pressure bar apparatus. The flow data obtained for NPH-718 alloy exhibited sensitivity to thermally activated processes. Consequently, as the temperature increased at a constant high loading rate, both flow stress and adiabatic effect increased. Conversely, at a constant deformation temperature, the flow characteristics exhibited an increase as the loading rate decreased. This study establishes key trends in the flow stress, adiabatic effect, temperature, and the strain rate sensitivities of NPH-718 alloy, offering valuable insights for design and performance evaluation purposes. It underscores the significant influence of temperature and strain rate on the flow behavior of NPH-718 alloy, further solidifying its reliability in demanding applications.